Quality of Life and Costs of Illness of Dengue Patients at Pku Muhammadiyah Yogyakarta and Bantul - Boisi, Cici Feronika; Purwanto, Barkah Djaka; Supadmi, Woro; Faridah, Imaniar Noor; Perwitasari, Dyah Aryani (Jurnal Ilmiah Farmasi, 2024)
Background: The manifestation of dengue is a decrease in hematocrit and platelet levels, leading to a decrease in the patient’s quality of life and having an impact on the patient’s medical costs.Objective: This study objective was to ascertain the quality of life and medical costs associated with dengue patients.Method: This study employed a cross-sectional design at PKU Muhammadiyah Hospitals in Bantul and Yogyakarta from January to August in 2023. Pediatric patients’ quality of life was assessed using the EQ-5D-Y questionnaire, while adult patients’ using the EQ-5D-5L questionnaire. Data on patients’ medical costs was obtained from the hospital's financial database. The data were then analyzed descriptively and presented as a percentage of quality of life and average medical costs.Results: The results showed that pediatric DF patients in both hospitals reported anxiety and depression, with percentages of 100% (Yogyakarta) and 75% (Bantul), respectively. Meanwhile, most adult DF patients experienced problems in carrying out routines, 71.4% (Yogyakarta) and 50% (Bantul), respectively. Adult DHF patients in both hospitals reported pain and discomfort of 66.7% (Yogyakarta) and 100% (Bantul), respectively. The highest average medical costs paid by DF and DHF patients at PKU Jogja Hospital were IDR 4,919,450 and IDR 6,981,500. DF and DHF patients at PKU Hospital with BPJS insurance, with the highest average medical costs of IDR 2,726,245.5 (for DF patients) and IDR 4,797,700 (for DHF patients) to cover for laboratory costs.Conclusion: Dengue fever infections are impacting the patient's quality of life and medical costs.